(untitled) (Research, Society and Development, 2021)
Science teaching is directly associated with involving students in activities that help them to understand abstract scientific models, making visual experiences fundamental in the teaching-learning process. In this perspective, visualization in science education presents a theoretical approach that seeks to understand the cognitive processes involved in activities that seek to favor these experiences, through visualization objects (such as graphs, tables, schematic diagrams). Among these visual experiences, we can consider the experimental activities, widespread in science teaching, developed in the concrete world and/or through digital technologies. Recent research (around the 2000s) has presented the scenario of integration of real experimental activities (concrete world) and virtual activities (digital technologies), in view of its use in isolated configurations. The comparative learning results have shown a promising scenario regarding the integration of these activities. Thus, the objective of this research was to analyze these results based on the visualization, through the visualization objects offered in the research activities. The results found confirmed our hypothesis that integration becomes more favorable to teaching, as it offers different visualization objects that become complementary. This scenario does not happen when using only one modality of experimental activity.